Temporal-spatial change characteristics of sunshine duration in Tibet based on spatial interpolation technique and its influence factors - YU Haijing; CHEN Tingfu; ZHANG Qingguo; ZHANG Ning; DONG Shijie; CHENG Mengdi (浙江大学学报. 农业与生命科学版, 2019)
In order to exploit and use solar energy resources, analyze the influence of climate change on sunshine duration, a spatial interpolation model was evaluated by various similarity coefficients and the optimal model was selected to study the spatial distribution characteristics of Tibet sunshine duration. Combined with sunshine duration of 52 meteorological stations in Tibet and the surrounding area during 1971 to 2015, the temporal change characteristics of sunshine duration in Tibet was analyzed. Results showed that the interpolation algorithm of Kriging spherical model could simulate Tibet sunshine duration quite well. The Tibet sunshine duration generally had a change tendency of gradual increase from east to west and from south to north. The Tibet’s annual sunshine duration had a decline tendency, and abnormal years mainly appeared in the 1980s. According to the topographic features of Tibet, the sunshine duration in the four areas was studied, which were Himalaya High Mountain (HHM), Eastern Tibet High Mountain (ETHM), Southern Tibet Lake Basin Valley Area (STLBA), Northern Tibet Plateau (NTP). The results showed that the annual sunshine duration of ETHM had a slight upward trend, other three areas showed a downward trend. The seasonal changes of sunshine duration in the four areas were as follows: In spring, NTP’s sunshine duration showed an increasing tendency. In summer, the sunshine duration of all the four areas showed a decline tendency. In autumn, the sunshine duration of all regions showed an increasing tendency except for NTP. In winter, the sunshine duration of all the four areas showed an increasing tendency. It was concluded that precipitation had the greatest impact on sunshine duration by analysis of four meteorological factors.